PENGEMBANGAN SISTEM INFORMASI TERINTEGRASI DALAM MENGELOLA SUKU CADANG GRUP MERO SEKAWAN MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT - Eugene Lainardy, Jevon
PT Mero Sekawan Jaya is a manufacturing company producing baking ingredients such as leavening agents, softeners, and cake fillings. The company has two subsidiaries, namely PT Calf Indonesia, focuses on cheese manufacturing, and PT Mercolade Indonesia, which specializes in chocolate manufacturing. These companies use various types of machines and equipment with different specifications in their production processes. However, for maintenance and repair activities, they use some spare parts with similar profiles Unfortunately, information about these spare parts is stored in different information systems across departments and companies, with varying formats. Therefore, there is a need to develop an integrated information system to facilitate communication and coordination for collaboratively managing the companies' spare parts, enabling an efficient reorganization of spare parts business processes across departments and companies. The development follows the Rapid Application Development (RAD) methodology, which includes planning, analysis and design, development, and implementation phases. First, the reorganization of business processes was modeled using Business Process Model and Notation (BPMN). Then, the information system modeling was done using a context diagram, decomposition diagram, and data flow diagram, which were visualized in a system flow that had been verified by stakeholders. On the other hand, the database system modeling was done using an Entity Relationship Diagram (ERD), built using DBMS software, namely SQL Server Management Studio on an SQL Express server. Finally, the information system development was carried out using the ASP.NET framework on the Microsoft Visual Studio IDE. The business process improvements cover the processes of requesting, fulfilling (including borrowing), purchasing (including collective purchasing), receiving, and reporting spare parts. The data flow modeling resulted in five subsystems within the information system, namely the receiving, requesting, management, purchasing, and reporting subsystems. System development was based on the verification results of the system flow, with critical programming mechanisms that include data retrieval, adding new data, updating data, and programming logic. Programming was performed on both the system interface, utilizing HTML, CSS, and JavaScript, as well as the backend (server) system using C# and SQL programming languages. The developed information system has been validated by system stakeholders.